A Recyclable Hydrophobic Anchor‐Tagged Asymmetric Amino Thiourea Catalyst. Issue 16 (11th July 2018) - Jichu, Takahisa; Inokuma, Tsubasa; Aihara, Keisuke; Kohiki, Taiki; Nishida, Kodai; Shigenaga, Akira; Yamada, Ken‐ichi; Otaka, Akira
Abstract: A novel, recyclable, thiourea‐based asymmetric organocatalyst containing a hydrophobic anchor has been developed. The chemical nature of the hydrophobic anchor contributes to the desirable characteristics of the recyclable catalyst. The hydrophobic anchor‐tagged thiourea catalyst is highly soluble in less polar solvents, which is compatible with amino thiourea catalyst‐mediated asymmetric reaction conditions, but sparingly soluble in polar solvents used for the recycle process. This asymmetric catalyst delivers a catalytic performance comparable to that of a parent catalyst and can be readily recycled from reactions. Abstract : Catalyst comes back : A novel, recyclable, thiourea‐based asymmetric organocatalyst containing a hydrophobic anchor has been developed. The hydrophobic anchor‐tagged thiourea catalyst is highly soluble in less polar solvents compatible with the amino thiourea catalyst‐mediated asymmetric reaction conditions, but insoluble in polar solvents so that the catalyst can be readily recycled only by simple filtration.